Transforming TRP Channel Drug Discovery Using Medium-Throughput Electrophysiological Assays. (March 2014) - Chambard, Jean-Marie; Tagat, Eric; Boudeau, Philippe; Partiseti, Michel
Since the cloning of its first member in 1998, transient receptor potential (TRP) cation channels have become one of the most studied ion channel families in drug discovery. These channels, almost all calcium permeant, have been studied in many different (patho)-physiological and therapeutic areas as diverse as pain; neurodegenerative, cardiovascular, and inflammatory diseases; and cancer. At the same time, implementation of automated electrophysiology screening platforms has significantly increased the tractability of ion channels, mainly voltage gated, as drug targets. The work presented in this article shows the design and validation of TRP screening assays using the IonWorks Quattro platform (Molecular Devices, Sunnyvale, CA), allowing a significant increase in throughput to support drug discovery programs. This new player has a direct impact on resources and timelines by prioritizing potential candidates and reducing the number of molecules requiring final testing by manual patch-clamp, which is still today the gold standard technology for this challenging drug target class.